Managing the university curriculum : making common cause (Buckingham, [England] ; Bristol, PA : Society for Research into Higher Education and Open University Press, 1994)
This book is divided into four parts: The changing context; Managing the University: Institutional heads; Managing the Curriculum: Middle managers and lecturers; Facing the Future.
Keywords: Education; Higher education; Curricula; Universities and colleges; Teacher participation in administration; Education, Higher -- Great Britain -- Curricula -- Congresses; Universities and colleges -- Great Britain -- Administration -- Congresses; Teacher participation in administration -- Great BritainxCongresses